Parvalbumin Interneurons and Perineuronal Nets in the Hippocampus and Retrosplenial Cortex of Adult Male Mice After Early Social Isolation Stress and Perinatal NMDA Receptor Antagonist Treatment - Klimczak, Patrycja; Rizzo, Arianna; Castillo-Gómez, Esther; Perez-Rando, Marta; Gramuntell, Yaiza; Beltran, Marc; Nacher, Juan (Frontiers in Synaptic Neuroscience, 2021)
Both early life aversive experiences and intrinsic alterations in early postnatal neurodevelopment are considered predisposing factors for psychiatric disorders, such as schizophrenia. The prefrontal cortex and the hippocampus have protracted postnatal development and are affected in schizophrenic patients. Interestingly, similar alterations have been observed in the retrosplenial cortex (RSC). Studies in patients and animal models of schizophrenia have found alterations in cortical parvalbumin (PV) expressing interneurons, making them good candidates to study the etiopathology of this disorder. Some of the alterations observed in PV+ interneurons may be mediated by perineuronal nets (PNNs), specialized regions of the extracellular matrix, which frequently surround these inhibitory neurons. In this study, we have used a double hit model (DHM) combining a single perinatal injection of an NMDAR antagonist (MK801) to disturb early postnatal development and post-weaning social isolation as an early life aversive experience. We have investigated PV expressing interneurons and PNNs in the hippocampus and the RSC of adult male mice, using unbiased stereology. In the CA1, but not in the CA3 region, of the hippocampus, the number of PNNs and PV+PNN+ cells was affected by the drug treatment, and a significant decrease of these parameters was observed in the groups of animals that received MK801. The percentage of PNNs surrounding PV+ cells was significantly decreased after treatment in both hippocampal regions; however, the impact of isolation was observed only in CA1, where isolated animals presented lower percentages. In the RSC, we observed significant effects of isolation, MK801 and the interaction of both interventions on the studied parameters; in the DHM, we observed a significantly lower number of PV+, PNNs, and PV+PNN+ cells when compared to control mice. Similar significant decreases were observed for the groups of animals that were just isolated or treated with MK801. To our knowledge, this is the first report on such alterations in the RSC in an animal model combining neurodevelopmental alterations and aversive experiences during infancy/adolescence. These results show the impact of early-life events on different cortical regions, especially on the structure and plasticity of PV+ neurons and their involvement in the emergence of certain psychiatric disorders.